The Role of διάνοια in Plotinus' Philosophy. - Gerson, Lloyd P. (International Journal of the Platonic Tradition, 2023)
In this paper, I explore the centrality of διάνοια in Plotinus' philosophy. Plotinus says that the real "we" is found to be the subject of διάνοια and "upwards." This fundamental definition elicits several pressing questions. First, how is the subject of discursive reasoning related to the subject of appetitive and affective states? Second, how does the subject of discursive reasoning come to recognize its ultimate destiny as an undescended and disembodied intellect? Finally, why should we think that, as Plotinus says, there is "no falsity" in discursive thinking? The answers to these questions begins with Plotinus' reflections on Plato's Divided Line and the sharp distinction between διάνοια and δόξα. I argue that διάνοια is the embodied expression of disembodied νοῦς. It is the focus of our ambiguous and conflicted personal identity.